Evaluasi Customer Relationship Management pada Supermarket Hero di Jakarta Timur - S. Liawatimena; M. F. Amanda; Handoko Handoko; Hendry Hendry (Bina Nusantara University, 2002)
The growing of many big retailer make Hero Supermarket must obtaining it’s existance in retail business. Therefore, Hero Supermarket must form CRM (Customer Relationship Management) in order to increase a new customer, increase profit and maintaining customer, and pay attention to valuable customer. Data analysis done by searching procentage from many questions and cartesius diagram. The conclusion, the highest suitable level there are 98,27% of quality product and the lowest is the price of merchandise, which is 45,35%. Some atribute are over the customers hope, that is good shopping place image, completeness, the comfortable and easyness in shopping, and safetyness. There are five most important atribut, that is the price, quality, completeness, the comfortable and easyness in shopping, and parking space. Those atribute will determine wether the customer of Hero Supermarket will be loyal or not.